a.
"Y=C+I+G""Y=C_o+C_1(Y-T)+b_o+b_1Y-B_2i+G"
"Y=C_o+C_1(Y-t_o-t_1Y)+b_o+b_1Y-b_2i+G"
"Y=C_o+C_1Y-C_1t_o-C_1t_1Y+b_o+b_1Y-b_2i+G"
"Y(1-C_1+C_1t_1-b_1)=C_o-C_1t_o+b_o-b_2i+G"
"Y=" "C_o-C_1t_o+b_o-b_2i+G \\over 1-C_1+C_1t_1-bi"
The multiplier is
b. "M \\over P" "= d_1Y-d_2i"
"i=" "d_1Y- { M\\over P} \\over d_2"
"Y="
"C_o-C_1t_o+b_o-b_2""(" "d_1Y- {M\\over P}" ")"
"Y=" "1 \\over 1-C_1+C_1t_1-b_1+{b_2\\over d_2} d_1"
The multiplier is
"1 \\over 1-C_1+C_1t_1-b_1+{b_2 \\over d_2} d_1"
multiplier at (b) is greater than multiplier at (a)
The curve becomes less steep as investment becomes more responsive to change in i. in other words, as b2 increases, the curve becomes steeper as money demand becomes more responsive to change in aggregate economic activity.
Comments
Leave a comment